Pengalaman guru terhadap penggunaan ChatGPT dalam pembelajaran di SMA - Alya Cindana; Hasrul Hasrul; Isnarmi Moeis; Rinia Zatalini (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This research is motivated by the growing use of artificial intelligence (AI) technology in education, particularly ChatGPT, which teachers are beginning to utilize to support the learning process. This study aims to analyze teachers' experiences in using ChatGPT in the learning process at SMAN 2 Lubuk Basung. The study used a qualitative approach with a descriptive research type. The research informants consisted of 14 teachers and 3 students selected using a purposive sampling technique. Data were collected through semi-structured interviews and document studies, then analyzed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that teachers' experiences in using ChatGPT fall into three main categories. First, ChatGPT is used to assist in the development of learning materials. Second, ChatGPT is used as a tool to compare and verify learning materials with other sources to ensure the appropriateness and accuracy of the information. Third, ChatGPT is used to clarify learning materials, particularly contextual and case-based materials, while remaining under teacher supervision. This study demonstrates that ChatGPT serves as a tool that supports the efficiency and effectiveness of learning, but does not replace the role of teachers in selecting, verifying, and developing learning materials.